FAKTOR YANG MEMPENGARUHI NILAI PERUSAHAAN MANUFAKTUR DENGAN PENGHINDARAN - Arfin Hanes Lim; Arles P Ompusunggu (Fakultas Ekonomi Universitas Tarumanagara, 2024)
This study aims to examine the effect of institutional ownership, company size, and managerial ownership on firmvalue with tax avoidance as a moderating variable in manufacturing companies listed on the Indonesia StockExchange for 5 years from 2015 to 2019. This research is quantitative with a sample selection method. namelypurposive sampling. Data processing uses multiple linear regression and moderated regression analysis (MRA)through the application of the Statistical Package for Social Science (SPSS) version 25.0. The results of this studyindicate that institutional ownership and managerial ownership do not have a positive effect on firm value. Meanwhile,firm size has a positive influence on firm value. The results of this study also conclude that tax avoidance cannotmoderate institutional ownership and managerial ownership of firm value. However, tax avoidance can moderate thesize of the company to the value of the company.